Eksistensi Hukum Adat dalam Politik Hukum Nasional pada Era Modernisasi Dewasa Ini - Made Dwiko Dentista Putra; I Ketut Sudantra (Asosiasi Penelitian dan Pengajar Ilmu Hukum Indonesia, 2024)
This study intended findout the existence of common law in national legal politics and to figure out more efforts that were done by the government and non-government so that common law and national l egal politics run in balance. This study made use of normative legal research with legislation and a comparative approach method. The results of the study indicated that common law does have different characters from national law, where national law has written characters in laws and regulations systematically and rigidly. Common law existence is recognized in national legal politics at the macro legal political level. In macro legal politics, recognition of common law community units and their traditional rights have been enshrined in the constitution, through Pasal 18B ayat (2) UUDNRI 1945. As is well known, common law communities are the bearers of common law.